Determination of the Prevalence of Knee and Hip Clinical Osteoarthritis in the Active Professional Male Footballer and Its Association with Pain, Function, Injury and Surgery - Lervasen Pillay; Dina C. Janse van Rensburg; Gopika Ramkilawon; Mario Maas; Emmanuel Orhant; Jussi Rantanen; Jari Salo; Gino Kerkhoffs; Vincent Gouttebarge (MDPI AG, 2023)
Objective: To comment on and explore (1) the prevalence of clinical knee and hip osteoarthritis (OA); (2) the association between pain or function and clinical knee or hip OA; (3) the association between injury or surgery and clinical knee or hip OA. Methods: Participants were recruited from FIFPRO members. A total of 101 footballers consented to answer (1) a developed questionnaire, (2) patient-reported outcome measures, and (3) be evaluated by their team physician for clinical knee or hip OA. Results: Of the 53% evaluated for clinical knee and hip OA, a prevalence of 9.43% and 7.55% of knee and hip OA, respectively, was found. There was a significant and strong association between knee (p = 0.033; Cramers v Value = 0.523) and hip pain (p = 0.005; Cramers v Value = 0.602) and clinical OA. A significant association existed between Hip dysfunction and Osteoarthritis Outcome short form Scores and clinical OA of the hip (p = 0.036). The odds of clinical knee OA were 1.5 and 4.5 times more after one or more injuries or surgeries, respectively. There was no association between playing position and clinical OA. Conclusion: There is a low prevalence of a clinical knee or hip OA in the active professional male footballer. Pain may be a valid symptom to predict or monitor knee or hip OA. Validated assessment tools should be utilised to identify a negative effect on function. The odds of developing clinical OA in the knee with the number of injuries or surgeries. The hip presents with earlier clinical signs of OA compared to the knee.